First record of the sea anemone Bunodosoma californicum (Cnidaria: Actiniaria) on the Pacific coast of Costa Rica - Quesada, Andres J. (2015)
We report the first record of the sea anemone Bunodosoma californicum on the Pacific coast of Costa Rica, extending its southern distribution. Four specimens were collected from an artificial breakwater in Mata de Limo´n, Puntarenas. We present images of the live specimens and analyses of their cnidae composition.